Parental perceptions of and concerns about child's body weight in eight European countries – the IDEFICS study. Issue 2 (21st September 2012) - Regber, S.; Novak, M.; Eiben, G.; Bammann, K.; De Henauw, S.; Fernández‐Alvira, J. M.; Gwozdz, W.; Kourides, Y.; Moreno, L. A.; Molnár, D.; Pigeot, I.; Reisch, L.; et al.
Summary: What is already known about this subject: Parents of children with overweight and obesity tend to underestimate their children's weight. Most studies show no association between parental education level and accurate parental perception of a child's weight category. Studies show no consistent relationship between parental weight perception and the child's gender. What this study adds: Parental underestimation of children's weight category for children in the overweight and obesity categories was found across eight European countries. Regional differences indicated a more accurate parental weight perception in Northern and Central Europe. A high proportion of parents in Southern Europe were concerned about future underweight or overweight in their children. Objectives: To evaluate parental perceptions of and concern about child's body weight and general health in children in a European cohort. Design: Cross‐sectional multi‐centre study in eight European countries. Participants: 16 220 children, ages 2–9 years. Methods: Parents completed a questionnaire regarding children's health and weight and concern about overweight and underweight. Objective children's weight categories from the International Obesity Task Force were used. Logistic regression models were utilized to identify predictors of accurate weight perception. Results: Parental weight perception corresponded overall to children's mean body mass index (BMI) z ‐scores, with important exceptions. About one‐third of the total indicated concern about underweight, paradoxically most often parents of children in the overweight or obesity categories. In 63%, parents of children in the overweight category marked 'proper weight'. The strongest predictor for accurate parental weight perception for children with overweight and obesity was BMI z ‐score (odds ratio [OR] = 7.2, 95% confidence interval [CI] 6.1–8.7). Compared to Southern Europe, ORs for accurate parental weight perception were 4.4 (95% CI 3.3–6.0) in Northern Europe and 3.4 (95% CI 2.7–4.2) in Central Europe. Conclusion: Parents of children categorized as being overweight or obese systematically underestimated weight. Parents differed regionally regarding accurate weight perception and concern about overweight and underweight.